Utilization of Landsat 8 Imagery and Dem Data to Determine the Level of Vulnerability and Mitigation of Rob Floods in the Pekalongan Region, Central Java - krisnandi, reza; Adi Prabowo (ReTII, 2021)
The northern coastal area of Pekalongan is an area that is often affected by tidal flooding or better known as tidal flooding. Geomorphologically, the Pekalongan region is located on the north coast of Java Island which has an alluvial plain and a flood plain. This study aims to zoning the distribution of tidal flooding based on the weighted value of the parameters on the north coast of Pekalongan, and to provide directions for tidal flood mitigation. The map processing process is supported by Landsat 8 imagery and DEM data. The research method used is in the form of scoring, weighting and overlay methods. The results of the study are flood vulnerability, high vulnerability is located in North Pekalongan Regency with a difference in height <5m (low) and a slope of 2-7% (ramps), vulnerability is located in Siwalan Regency with a difference in height of 5-50 m (moderate), and slopes. a slope of 2-7% (sloping), while low vulnerability is located in Tirto District with a difference of> 50 m (height), and 8-13% (slope). The tidal flood mitigation stage consists of 2 stages, namely structural mitigation and non-structural mitigation Keywords: Landsat 8 & DEM, vulnerability, mitigation, Pekalongan, zoning.